Quantitative assessment of pathways to a resource-efficient and low-carbon Europe - Martin Distelkamp; Mark Meyer (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2016)
Though the sustainability research community as well as international decision makers seem to share the conviction that, akin to the challenges of climate policy, a great transition will also be needed in order to decouple human wellbeing from resource use over the next decades, there exist only scarce quantitative assessments of possible transition scenarios which do also concern this matter. Our paper is intended to advance this branch of research by a presentation of key scenario insights from the global simulation model GINFORS which take account of the complex interrelations between different environmental objectives. Whereas a multitude of publications already applied various MRIO databases for ex post assessments of resource-related national footprint indicators, there exist only scarce ex ante assessments of possible transition scenarios concerning this matter. The modelling framework of GINFORS also rests on a MRIO database. Thus, GINFORS is also able to map quantitative indicators of material extractions embedded in regional consumption activities over the global supply chain.
Keywords: Q34; Q37; Q51; Q56; 330; raw material consumption; RMC; raw material input; RMI; CO2 emissions; macro-econometric model; GINFORS; MRIO; WIOD; policy simulations; resource-efficiency; low-carbon economy